When is Offspring Viability Fitness a Measure of Paternal Fitness and When is it not?. (29th November 2021) - Fitzpatrick, Courtney L; Wade, Michael J
Abstract: We use population genetics to model the evolution of a gene with an indirect effect owing to paternal care and with a second pleiotropic, direct effect on offspring viability. We use the model to illustrate how the common empirical practice of considering offspring viability as a component of parent fitness can confound a gene's direct and indirect fitness effects. We investigate when this confounding results in a distorted picture of overall evolution and when it does not. We find that the practice has no effect on mean fitness, W, but it does have an effect on the dynamics of gene frequency change, ∆q. We also find that, for some regions of parameter space associated with fitness trade-offs, the distortion is not only quantitative but also qualitative, obscuring the direction of gene frequency change. Because it affects the evolutionary dynamics, it also affects the expected amount of genetic variation at mutation-selection balance, an important consideration in molecular evolution. We discuss empirical techniques for separating direct from indirect effects and how field studies measuring the value of male paternal care might be improved by using them.